2019
DOI: 10.1016/j.healun.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Survival in pulmonary hypertension due to chronic lung disease: Influence of low diffusion capacity of the lungs for carbon monoxide

Abstract: BACKGROUND: Patients with pulmonary hypertension (PH) due to chronic lung disease (Group 3 PH) have poor long-term outcomes. However, predictors of survival in Group 3 PH are not well described. METHODS: We performed a cohort study of Group 3 PH patients (n = 143; mean age 65 ± 12 years, 52% female) evaluated at the University of Minnesota. The Kaplan–Meier method and Cox regression analysis were used to assess survival and predictors of mortality, respectively. The clinical characteristics and survival were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
0
30
1
1
Order By: Relevance
“…23 Similar findings have been reported in patients with chronic lung disease and PH. 2426 Suda et al. described a decreased DLCO to be associated with poor outcome in 91 medically treated CTEPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…23 Similar findings have been reported in patients with chronic lung disease and PH. 2426 Suda et al. described a decreased DLCO to be associated with poor outcome in 91 medically treated CTEPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A cohort study in patients with PH-CLD reported 1-, 3-, and 5-year survival rates of 79%, 48%, and 31%, respectively. 15 Patients with more severe lung disease and severe PH have a poor prognosis. 6 In an international CTEPH registry, 3-year survival was 90% in patients who underwent pulmonary thromboendarterectomy (PTE) and 70% in those who did not.…”
Section: Prognosis Of Patients With Phmentioning
confidence: 99%
“…It has been suggested that there is a pulmonary vascular phenotype of COPD patients. These patients have less severe airflow limitation, more severe hypoxaemia, very low diffusing capacity and cardiovascular exercise limitation [ 77 , 78 ]. It is recommended that COPD patients should be evaluated for PH when it has an impact on patient management, i.e.…”
Section: Pulmonary Treatable Traits In Severe Copdmentioning
confidence: 99%